Comprehensive Coagulation Profiling at the Point-of-Care Using a Novel Laser-Based Approach - Nadkarni, Seemantini K. (Seminars in Thrombosis and Hemostasis, 2019)
Delays in identifying internal bleeding are life-threatening, thus underscoring the need for rapid and comprehensive coagulation profiling at the bedside. The authors review a novel optical coagulation profiler that measures several coagulation metrics including prothrombin time, activated clotting time, clot polymerization rate (α-angle), clot stiffness (maximum amplitude), fibrinolysis (LY), and platelet function, using a single multifunctional instrument. The optical profiler is based on the principles of Laser Speckle Rheology that quantifies tissue viscoelasticity from light scattering patterns called laser speckle. To operate the optical profiler, whole blood (40 μL) is loaded into a disposable cartridge, laser speckle patterns are recorded via a camera, and the viscoelasticity of clotting blood is estimated from speckle intensity fluctuations. By monitoring alterations in viscoelastic moduli over time during clot initiation, thrombin generation, fibrin crosslinking, clot stabilization, and LY, global coagulation parameters are obtained within 10 minutes using a drop of whole blood. Clinical testing in over 500 patients to date has confirmed the accuracy of the optical profiler for comprehensively assessing coagulation status against conventional coagulation tests and thromboelastography. Recent studies have further demonstrated the capability to quantify platelet aggregation induced by adenosine diphosphate in a drop of platelet-rich-plasma in the absence of applied shear stress. Together, these studies demonstrate that global coagulation profiling in addition to platelet function may be accomplished using a single multifunctional device. Thus, by enabling rapid and comprehensive coagulation and platelet function profiling at the bedside, the optical profiler will likely advance the capability to identify and manage patients with an elevated risk for hemorrhage.
Keywords: coagulation; laser speckle; point of care; viscoelastic; platelet